Cardiac surgery using a single thoracic port—current status and future directions - Gallego-Poveda, Javier; Guerra, Nuno Carvalho; Gonzalez-Rivas, Diego; Carvalheiro, Catarina; Ferreira, Hugo; Sena, André; Junqueira, Nádia; Velho, Tiago Rodrigues; Nobre, Ângelo (Journal of Thoracic Disease, 2017)
Cardiac surgery is almost universally performed through a median sternotomy, an approach which is painful, unestethical, and prone to life-threatening infections. Minimally invasive cardiac surgery has tried to avoid problems associated with full sternotomy for many years. Recently, uniportal thoracic surgery was shown to be very advantageous when compared to standard thoracotomy and classical video assisted thoracic surgery (VATS). Despite very good results in lung surgery, cardiac surgery through a single thoracic port has rarely been attempted and successfully conducted. The authors present the rational, the technique, and their experience in cardiac single thoracic port surgery (CSTPS).